Ёш курашчиларнинг жисмоний сифатлари ва уларнинг физиологик хусусияти (SCIENCE and SOCIETY, 2016)
The article analyzes the physical and physiological characteristics of young wrestlers in the process of their preparation for competitions. There have been substantiated an important role of the potential of young fighters.